Kajian Teori Hubungan Disiplin dan Lingkungan Kerja dengan Kinerja Guru - Sarah Wulan (LPPM STKIP Kusuma Negara, 2016)
This study aims to determine: (1) the relationship between the discipline with performance, (2) relationship between the work environment with performance(3) the relationships between the discipline and work environment together with performance. The method used was library research. The results of research found that: (1) there is a positive relationship between the discipline with performance (2) there is a positive correlation between work environment with performance (3) there is a positive relationship between the discipline and work environment together with performance. This research concluded that (1) getting better discipline, the performance of teachers is higher, (2) the more condusif of work environment, the performance of teachers is higher, (3) The better discipline and the more condusif of work environment, the teachers have higher performance.